CHARACTERISTICS OF SOIL CHEMICAL PROPERTIES OF MANGO PLANTS IN TULAP COASTAL COAST, KOMBI DISTRICT, MINAHASA REGENCY - Wahyudi Ibrahim; Diane D. Pioh; Joice M. Supit (Jurnal Agroekoteknologi Terapan, 2022)
Soil chemical properties are very influential in increasing plant growth. Providing fertilizer is one of the important means of production in plant cultivation, so its availability is absolutely necessary for the development of soil and plants. The function of chemical fertilizers is to provide macronutrients such as N, P, K, Ca, Mg, and S and micronutrients such as Zn, Cu, B, Mo, Co, Mn, Fe. This study aims to determine the chemical properties of the soil planted with mango (Mangifera Indica L.) in Tulap Village, Kombi District, Minahasa Regency.The results showed that the pH content of the soil was in an acidic condition (6.5), C- organic had a very low to low content value (0.42% - 1.81 %), Nitrogen had a very low to low content value (0, 04 % - 0.16 %), Soil phosphorus has a moderate content value (20.09 ppm - 22.98 ppm), Potassium is available. Based on the chemical properties of the soil, the land planted with mango (Mangifera Indica L.) in Tulap Village, Kombi District has problems with organic C- and Nitrogen content, for that it needs to be improved.Keywords: Characteristics, Chemical Properties, Mango Plants.AbstrakSifat kimia tanah sangat berpengaruh untuk meningkatkan pertumbuhan tanaman. Pemberian pupuk merupakan salah satu sarana produksi penting dalam budidaya tanaman, sehingga ketersediaannya mutlak diperlukan untuk keberlanjutan produktivitas tanah dan tanaman. Fungsi pupuk kimia yaitu sebagai penyedia hara makro seperti N, P, K, Ca, Mg, dan S dan mikro seperti Zn, Cu, B, Mo, Co, Mn, Fe. Penelitian ini bertujuan untuk mengetahui karakteristik sifat kimia tanah yang ditanami tanaman mangga (Mangifera Indica L.) di Desa TulapÂ  Kecamatan Kombi Kabupaten Minahasa.Hasil penelitian menunjukkan bahwa kandungan pH tanah berada pada kondisi asam (6,5) , C-organik memiliki nilai kandungan sangat rendah hingga rendah (0,42 % - 1,81 %), Nitrogen memiliki nilai kandungan sangat rendah hingga rendah (0,04 % - 0,16 %), Fosfor tanah memiliki nilai kandungan sedang (20,09 ppm â€“ 22, 98 ppm), Kalium tersedia . Berdasarkan sifat-sifat kimia tanah lahan yang ditanami tanaman mangga (Mangifera IndicaL.) di Desa Tulap Kecamatan Kombi mempunyai permasalahan pada kandungan C-organik dan Nitrogen, untuk itu perlu diberikan perbaikan.Kata Kunci: Karakteristik, Sifat Kimia, Tanaman Mangga